A gestão da ficha de comunicação do aluno infrequente - FICAI - e a contribuição do serviço social para a garantia do direito à educação - Falcão, Eliete Ribeiro (2014)
This dissertation is related to the research area in Management, Education and Public Policies. Its main purpose is to investigate the flow processing of the FICAI online system (a communication form for infrequent students), considering the association between the National Education Guidelines and Framework Law (LDB/1996) and the Organic Law of Social Welfare (LOAS/1993) on ensuring school attendance. This flow presents the network service of the Unified System of Social Welfare (SUAS), with emphasis on the integration of the Social Welfare Reference Center (CRAS) and of the Specialized Social Welfare Reference Center (CREAS). The theory of reference discusses the FICAI management and its correlations with the Public Policy of Social Welfare, as well as the legal assumptions, which the FICAI management is based on, by analyzing the available instruments and individuals involved in operating this instrument. The empirical and exploratory field studies were based on the dialectical method, which allowed the analysis of the responses to the questionnaires of Prova Brazil 2011 and the interviews with pedagogical counselors of four public schools in the city of Canoas- RS, named by the City Department of Education. Therefore, the dissertation aims to understand how the public instruments of Social Welfare and the schools manage the FICAI demands, and the possible correlations between Science Education and Social Welfare for the production of more effective interdisciplinary knowledge to prevent school evasion, emphasizing the contributions of Social Welfare to guarantee real access to education.